(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The state of Gujarat, deeply rooted in the ideology of Mahatma Gandhi, has upheld alcohol prohibition for decades. While intended to curb alcohol consumption and associated social issues, the law has instead given rise to a thriving underground liquor economy, systemic corruption, and economic losses. This research critically analyzes the current state of alcohol prohibition in Gujarat, its impact on crime, public health, governance, and revenue generation. By evaluating legal challenges, societal perceptions, and policy alternatives, this study aims to present a balanced view of prohibition and whether reforms are necessary.